İslam hukukunda Hz. Peygambere hakaret suçu ve cezası - Yıldız, Hasan Basri (My University, 2019)
İslâm inancına göre peygamberler saygı duyulması gereken insanların en başında yer almaktadır. Bununla birlikte peygamberlerin sonuncusu olan Hz. Peygamber diğer peygamberler gibi gerek yaşadığı dönemde gerekse vefatından sonra bazı kimseler tarafından hakarete maruz kalmıştır. Bu araştırma İslâm hukukunda Hz. Peygamber’e hakaret suçu ve cezasını içermektedir. Amacımız İslâm hukukunda Hz. Peygamber’e hakaret suçu için öngörülen cezaları ortaya koymaktır. Çalışma biri giriş olmak üzere dört bölümden oluşmaktadır. Giriş bölümünde araştırmanın konusu, kapsamı, önemi, amacı, yöntemi, kaynakları, hakaret suçuyla alâkalı kavramlar ve Hz. Peygamber’in değeri hakkında bilgi verdik. Birinci bölümde hakaret suçunun unsurlarına, gerçekleşme şekillerine, fâilinde aranan şartlara, tespitine, hakaret eden Müslümanın hükmüne, hakaret eden zimmînin akdinin durumuna ve hakaret edenin pişmanlığına yer verdik. İkinci bölümde Hz. Peygamber’e hakaretin cezasını, cezayı ağırlaştıran, hafifleten veya ortadan kaldıran sebepleri ve tarihi uygulamaları ele aldık. Üçüncü bölümde ise Hz. Peygamber’e hakaretin cezası ile alakalı çağdaş yaklaşımları inceledik.

According to the Islamic Faith, the prophets are at the top of people who deserve to be respected. However, Muhammad (pbuh) like all the other messengers of Allah has been insulted by some people either in his time and after his death. This research includes the crime of insulting Prophet Muhammad and its punishment in Islamic law. The main goal of thesis is to reveal the punishments for insulting the Prophet in Islamic law. The study consists four chapters. The first one is introduction section. In the introduction, we gave information about the subject of the research, the scope, importance, purpose, method, resources, concepts related to the crime of insult and the value of the Prophet Muhammad (pbuh) in Islamic knowledge. In the first chapter, we have included elements of defamation crime, the manner of realization, the conditions of the insulting person, the determination, the judgment of the insulting Muslim, the state of the insulting dhimmi and the regret of the insulting person. In the second section, we discussed the punishment for insulting the Prophet, the reasons that aggravate, alleviate or eliminate the punishment and the historical practices. In the third chapter, we examined contemporary approaches to the punishment of the Prophet.
Keywords: Ceza Prophet; Crime; Hakaret; Insulting; Islamic law; İslam hukuku; Peygamber; Punishment; Suç